Current status and prospects of aviation remanufacturing technology based on cold spray - CHI Yada; CUI Minchao; LUO Ming; LI Wenya; ZHANG Dinghua (Hangkong gongcheng jinzhan)
Cold spray additive manufacturing technology，with its unique "solid-state deposition" process characteristics，has shown great application potential in the repair and remanufacturing of damaged aerospace structures. For components remanufactured using cold spray，the manufacturing quality depends on the bonding strength at the substrate interface，the structural integrity within the deposition body and the final processed surface quality. This article focuses on the entire cold spray remanufacturing process，aiming to introduce more universal high-performance cold spray remanufacturing methods from three aspects：substrate surface pretreatment，strengthening techniques for the cold spray deposit，and post-treatment of the cold spray deposit. In addition，existing cases of cold spray additive repair and remanufacturing in the aerospace sector both domestically and internationally are introduced，and the remaining issues and future development directions in the field of aerospace remanufacturing are prospected.